Reading Online in Foreign Languages: A Study of Strategy Use - Cheng, Richard (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2016)
Scores of studies have established that when learning online, students must be equipped with different sets of strategies and skills than in a physical classroom setting (Anderson, 2003; Broadbent & Poon, 2015; Coiro, 2007; Leu et al., 2007; Michinov, Brunot, Le Bohec, Juhel, & Delaval, 2011; Salmon, 2013). The present study, by virtue of exploring foreign language learners’ online reading experience, aimed to identify the reading strategies that learners would use when engaged in online reading activities in the target foreign languages. Thirty-two foreign language learners whose native language was English participated in the study. The Online Survey of Reading Strategies (OSORS) designed by Anderson (2003) was administered to investigate the following four research questions: (1) What are the strategies that language learners would or would not use when reading online in foreign languages? (2) Would foreign language learners use some of the online reading strategies more frequently than other strategies? (3) Would different levels of foreign language proficiencies influence language learners’ use of the strategies? (4) What could foreign language teachers do in their instruction to help students acquire and broaden their repertoire of online reading strategies? Data analysis demonstrated the most and least frequently used strategies of the foreign language learners and uncovered a significant difference in the frequency of use among the strategies. However, there was no significant difference found between the use of online reading strategies and learners’ foreign language proficiencies. Implications and suggestions for future research and practice were proposed accordingly.